The representation of law enforcement authorities’ performance in NBC News coverage of the Debanhi Escobar case: A dialectical relational approach - Wicaksana, Rachim Satria; Nurhayati, Nurhayati; Sere, Istiqamah Idrus (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2026)
NBC News, as an international media outlet, plays a significant role in shaping public perception and moral evaluation of social issues. Its coverage of the Debanhi Escobar case in Mexico has attracted widespread international attention, particularly in relation to the handling of feminicide by Law Enforcement Authorities. Within this context, the present study investigates how NBC News represents Law Enforcement Authorities in reporting the Debanhi Escobar case and how such representations construct moral and institutional evaluations. This study applies Fairclough’s Dialectical Relational Approach (DRA) to examine the relationship between textual strategies, social practices, and power relations embedded in media discourse. In addition, Appraisal Theory is employed to analyze evaluative language and to uncover the underlying moral and ethical positioning conveyed in the news reports. The data are drawn from publicly accessible NBC News articles and are analyzed using a qualitative descriptive method, supported by multimodal analysis. The findings indicate that the victim is foregrounded through the narration of violent events and moral evaluations expressed via direct, indirect, and narrative speech. In contrast, Law Enforcement Authorities are predominantly represented through heteroglossic voices, irony, and weak epistemic modality, which contribute to negative judgment and foster skepticism toward institutional credibility. These discursive practices suggest that NBC News operates not merely as an information provider but as an active social and evaluative agent. Overall, this study demonstrates that the integration of DRA and Appraisal Theory provides a comprehensive framework for examining international media discourse and its role in promoting social accountability.